A New Binuclear Cobalt(II) Complex Based on 1, 3-Benzenedicarboxylic Acid and 2-(3-Pyridyl)benzimidazole. Issue 4 (2nd April 2016) - Zhang, Quanzheng; Xia, Changkun; Lu, Hongdian; Jiang, Rui; Zhang, Xueke; Wang, Xinghan; He, Longzhong
Abstract : A binuclear cobalt(II) complex, [Co2 (H2 O)4 (3-PBIM)4 (1, 3-BDC)2 ]·2H2 O (1, 3-H2 BDC = 1, 3-benzenedicarboxylic acid, 3-PBIM = 2-(3-pyridyl)benzimidazole), has been synthesized and characterized by elemental analysis, IR and single-crystal X-ray diffraction. The crystallographically independent cobalt atom is coordinated by four oxygen and two nitrogen donors in an octahedron geometry ([CoN2 O4 ]). Two cobalt coordination units ([CoN2 O4 ]) are linked together via four carboxyl oxygen atoms of two 1, 3-BDC 2− ligands, forming a dimetal unit ([CoN2 O4 ]2 ). The extensive hydrogen bonding interactions connects the binuclear metal units into three-dimensional framework.